TEACHING READING COMPREHENSION TO EFL JUNIOR HIGH SCHOOL STUDENTS - Maulizan Maulizan (Universitas Syiah Kuala, 2015)
Teachers have a vital role in the teaching learning process; their role supports the development of students’ competency through learning. A teacher is required to possess comprehensive knowledge in pedagogy. In fact, a teacher can choose from a variety of methods to teach reading. In this study the researcher tried to find out the relationship between theory and facts. This study used descriptive research methods. The populations of this study were the English teachers and students in a junior high school in Banda Aceh. The instruments used were: observation sheets, questionnaires and interviews. Based on the data gathered, the researcher found several problems that needed to be solved, even though the teachers at the junior high school in Banda Aceh already had standard knowledge in teaching, especially in preparing lesson plans, but, they lacked the ability to implement their knowledge especially in teaching reading comprehension. Based on observations the researcher concluded that the methods and strategies generally applied by the teachers at the school were: Direct Method, Grammar Translation Method and Think Pair Share Method, which still required supervision. Therefore, the researcher hopes that this study can be continued by subsequent researchers in the future in order to provide more input for better implementation of methods in teaching English, especially for teaching reading comprehension.